Detection of Diazotrophy in the Acetylene-Fermenting Anaerobe Pelobacter sp. Strain SFB93 - Akob, Denise M. (Appl Environ Microbiol, 2017)
Acetylene (C(2)H(2)) is a trace constituent of the present Earth's oxidizing atmosphere, reflecting a mixture of terrestrial and marine emissions from anthropogenic, biomass-burning, and unidentified biogenic sources. Fermentation of acetylene was serendipitously discovered during C(2)H(2) block assays of N(2)O reductase, and Pelobacter acetylenicus was shown to grow on C(2)H(2) via acetylene hydratase (AH). AH is a W-containing, catabolic, low-redox-potential enzyme that, unlike nitrogenase (N(2)ase), is specific for acetylene. Acetylene fermentation is a rare metabolic process that is well characterized only in P. acetylenicus DSM3246 and DSM3247 and Pelobacter sp. strain SFB93. To better understand the genetic controls for AH activity, we sequenced the genomes of the three acetylene-fermenting Pelobacter strains. Genome assembly and annotation produced three novel genomes containing gene sequences for AH, with two copies being present in SFB93. In addition, gene sequences for all five compulsory genes for iron-molybdenum N(2)ase were also present in the three genomes, indicating the cooccurrence of two acetylene transformation pathways. Nitrogen fixation growth assays showed that DSM3426 could ferment acetylene in the absence of ammonium, but no ethylene was produced. However, SFB93 degraded acetylene and, in the absence of ammonium, produced ethylene, indicating an active N(2)ase. Diazotrophic growth was observed under N(2) but not in experimental controls incubated under argon. SFB93 exhibits acetylene fermentation and nitrogen fixation, the only known biochemical mechanisms for acetylene transformation. Our results indicate complex interactions between N(2)ase and AH and suggest novel evolutionary pathways for these relic enzymes from early Earth to modern days. IMPORTANCE Here we show that a single Pelobacter strain can grow via acetylene fermentation and carry out nitrogen fixation, using the only two enzymes known to transform acetylene. These findings provide new insights into acetylene transformations and adaptations for nutrient (C and N) and energy acquisition by microorganisms. Enhanced understanding of acetylene transformations (i.e., extent, occurrence, and rates) in modern environments is important for the use of acetylene as a potential biomarker for extraterrestrial life and for degradation of anthropogenic contaminants.